Penerapan Ice Breaking untuk Memaksimalkan Konsentrasi Siswa Sekolah Dasar pada Awal Jam Pelajaran (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
This study aims to examine the role of ice breaking in improving students' learning focus at the beginning of the lesson, especially at the elementary school level. Icebreaking is a learning technique that aims to prepare students mentally and emotionally to receive lessons by creating a cheerful, relaxed, and enjoyable classroom atmosphere. This study investigated various literatures, including scientific journals and educational articles. The results of the study showed that turning ice was proven to be effective in improving students' concentration, enthusiasm, and social interaction. Ice breaking not only makes the atmosphere better, but can also improve student learning outcomes. Therefore, ice breaking can be used as a learning strategy to make elementary schools a good place to learn.